PENGEMBANGAN E-MODUL BERBASIS APLIKASI ANDROID SEBAGAI SUMBER BELAJAR DARING PADA MATERI DINAMIKA ATMOSFER - Rival Navigas (JURNAL BUANA, 2022)
This study aims to determine how the development of an android application-based electronic module using the Plomp development model and to find out its practicality. Development aims to make the product can be used as a learning reasource for online learning. The type of research used is the ype of research development or R&D. With the population are students of class X Lareh Sago Halaban highschool The results of research is resulted a e-module product with a plomp development model. The result of content validation get 85%, 95% for design validation and 91%for language validation.Then the result of product wew tried out on 91 grade X students who were undoing online learning and got 75,8% practicality ponts which were referred to the product Likert eligibility table declared is practical. The result of effectiveness test got 81,3% and got title of effective